The Securitization of Australian Migration during the Prime Minister Malcolm Turnbull's Presidency - Farabi, Nadia; Saraswati, Dinda Ayu (Department of International Relations Universitas Pertamina, 2024)
Humanitarian aspects on the issue of migration were re-introduced during the reign of Prime Minister Malcolm Turnbull through the regional instrument of Bali Declaration. Although Australia has long ratified the 1951 UN Convention relating to the status of refugees, some of Australia's political efforts have previously been contrary to the principles of the convention. Therefore, this research intends to describe the process that forms political efforts during the reign of Prime Minister Malcolm Turnbull and to determine the factors that shape the dynamics of perception regarding the issue of migration in Australia. To analyze the process, this research uses the concept of securitization with qualitative method and descriptive research by using literature review in data collection. The results show that during the reign of Prime Minister Malcolm Turnbull the issue of migration was framed as a security issue by considering the balance between border protection and fulfillment of international obligations.